Salicylic acid can trigger sugarcane resistance to leaf scald under water deficit stress - da Silva Souza, Lucas [UNESP] (2025)
Leaf scald disease negatively affects sugarcane production worldwide. In addition to that, abiotic stresses such as water deficiency, which can also cause crop production losses, facilitates the emergence of leaf scald acute symptoms, increasing damages to the plants. Currently, the only effective method of controlling this disease is the use of resistant cultivars. However, as resistance can be easily broken by the pathogen, new methods are required to help controlling the disease, with the search for alternative means of control becoming of great importance, such as the induction of resistance. Recent studies have proven that salicylic acid (SA) has the potential to induce resistance against pathogens in different crops. Therefore, this study aimed to evaluate the use of SA foliar applications in order to help control leaf scald in sugarcane under water deficit. Two sugarcane cultivars were used, one being resistant (SP80-3280) and another susceptible (SP78-4467) to this disease. Before inoculation, all plants were subjected to SA applications for 90 days, being later on inoculated with the pathogen (Xanthomonas albilineans), as well as subjected or not to water deficit. Both stresses (biotic and abiotic) caused a drop in chlorophyll and carotenoids content. Besides that, treatments that also underwent water deficit had lower leaf water potential, with SA applications promoting an increase in this parameter for the resistant cultivar, since SA is related to the induction of genes present in drought-resistant cultivars. SA also promoted an increase in proline concentration, as well as in superoxide dismutase (SOD), guaiacol peroxidase (GPOX) and glutathione peroxidase (GSH-Px) activities in both cultivars when plants were inoculated and under water deficit. In general, SA applications attenuated the damages caused by the pathogen and water deficit, with the susceptible cultivar being the most responsive to its applications.